The Effect of Stock Price, Stock Trading Volume and Market Capitalization on the Stock Return of Health Sector Companies Listed on the Indonesia Stock Exchange during Covid 19 (Period 2020-2022) - Elsye Fatmawati; Parulian Parulian (Daengku: Journal of Humanities and Social Sciences Innovation, 2024)
The purpose of this study was to analyze the effect of stock prices, stock trading volume and market capitalization on stock returns of health sector companies listed on the Indonesia Stock Exchange (IDX) during the Covid 19 period (2020-2022 period). The capital market is a place where investors can provide a portion of their capital to invest in a company issuer to gain profit. The type of research used in this study uses quantitative research, namely research conducted using numbers as objects in conducting analysis. The data used is secondary data in the form of quarterly data over a period of 3 years. The samples used in this study were 17 health sector companies listed on the Indonesia Stock Exchange. As for the data collection method by means of documentation and sampling using purposive sampling method. The results of this study indicate that the stock price variable has a significant level of value on stock returns with the results of the t test which is worth 0.000 so it can be interpreted that the stock price variable has a significant effect on stock returns. The stock trading volume variable has a significant effect on stock returns, this can be seen by the significance value of the t test results of 0.042. The market capitalization variable has no significant effect on stock returns, this can be proven by the significance value of the t-test results of 0.212.